An auto ethnographic account of one woman’s experience on school retention as a female student in Uganda. - Lolem, Benna (Trinity College (Dublin, Ireland). School of Education, 2021)
ABSTRACT. I am the living embodiment of the experiences of one female student, teacher, wife, mother and educator living with female students who are still in school. My interest in this thesis is in those female students who have dropped out of secondary school for one reason or another. The research objectives are categorised in two types, the general and specific objectives. The general objective was to: investigate some of the factors that contribute to female student drop out from secondary schools in Uganda by examining a single example.The specific objectives of this study were to: 1. Investigate economic factors that lead to female student drop out from secondary school 2. Determine the social and cultural factors that lead to female students drop out from secondary school 3. Examine school based factors that may lead to female student drop out from secondary school. In this study, I use the methods and approach of auto ethnography. To try to understand the contributing factors to female student drop out from secondary schools. By examining the factors and influences in my personal lived experience, I want to see how drop out can be minimised. The research adopted a qualitative study approach to best capture the lived experiences of the researcher herself based on an auto ethnographic study as a methodology through which, personal letters ,documents, artefacts and recollections of contemporaries were reviewed and a recollection of important events in the researchers’ life were made in the process of account making. The study revealed a number of the underlying factors contributing to female student dropout in Uganda. Research indicates that, it is a global phenomenon experienced in both developed and developing countries. A study by Ngara (2015), noted that approximately ten million girls globally are trapped in early or forced marriages an equivalent of one girl in every three seconds. Pregnancy among girls In addition to excess punishments, lack of privacy, sexual abuse by male teachers among others contributed to dropout Rutakiniwa ( 2016).
Keywords: Leadership and Management in Education; Education